Uniaxial negative thermal expansion in the [(CH3)2NH2]PbBr3 hybrid perovskite. Issue 46 (7th November 2022) - Rodríguez-Hernández, Juan S.; P. Gómez, Mayra A.; Abreu, D. S.; Nonato, Ariel; da Silva, Rosivaldo Xavier; García-Fernández, Alberto; Señarís-Rodríguez, María A.; Sánchez-Andújar, Manuel; Ayala, A. P.; Paschoal, C. W. A.
Abstract : The [(CH3 )2 NH2 ]PbBr3 perovskite exhibits an unusual thermal expansion, and we propose a novel thermomechanical mechanism that differs from the typical " wine-rack ". Also, we probed the presence of an H-bond between the DMA cation and the framework. Abstract : We have investigated the first-order structural phase transition undergone by [(CH3 )2 NH2 ]PbBr3 at T = 250 K and its lattice dynamics using both temperature-dependent synchrotron X-ray powder diffraction (SXRPD) and Raman spectroscopy techniques. Very interestingly, we find that this compound exhibits an unusual uniaxial thermal expansion, which we relate to the structural arrangement of the bioctahedron [Pb2 Br9 ] 5− units in this 4 H -hexagonal perovskite, which favors the elongation of the PbBr3- framework parallel to the ab plane, and the shrinkage of the bioctahedron [Pb2 Br9 ] 5− units along the crystal c -axis upon heating. This novel thermomechanical mechanism differs from the typical "wine-rack" one described so far in other perovskite materials. Additionally, we have studied the lattice dynamics in this compound by Raman spectroscopy, probing the presence of a H-bond between the DMA cation and the framework. Our findings suggest that intermolecular interactions weaken upon heating, which plays a fundamental role in the phase transition to the disordered high-temperature phase.